New Species of Collembola of the Genus Arrhopalites (Entognatha, Hexapoda) from a Cave in Eastern Carpathians - Vargovich, R.S. (Вестник зоологии, 1999)
A new troglobiont species of the genus Arrhopalites Bomer, 1906 (Collembola, Arrhopalitidae) from Ukrainian (Eastern) Carpathians is described. Arrhopalites car-pathicus sp. n. belongs to the pygmaeus group but differs from other known species by the presence of 7—8 subsegments of Ant. IV and bifurcated, laterally serrated female anal appendages. Описан новый троглобионтный вид рода Arrhopalites Bomer, 1906 (Collembola, Arrhopalitidae) из Украинских (Восточных) Карпат. Arrhopalites car-pathicus sp. n. принадлежит к группе видов ру$таеиз\ отличается от других известных видов присутствием 7—8 субсегментов на Ап1. IV, раздвоенными и латерально зазубренными анальными придатками самки.